2015
DOI: 10.1007/s10067-015-3140-6
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab-induced autoantibodies: a multicenter study

Abstract: The purpose of this study was to assess autoantibody incidence in patients treated with infliximab for various diseases, and the development of autoimmune diseases using a multicenter, longitudinal, open-label, phase IV observational study. All patients received anti-tumor necrosis factor (anti-TNF) according to local treatment guidelines. The autoantibodies assessed before and after infliximab treatment were ANA, anti-Sm, anti-dsDNA, anticardiolipin IgM/IgG, anti-Scl70, anti-centromere B, anti-chromatin, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…IFX is a chimeric anti-human TNF monoclonal antibody [124] use to treat autoimmune diseases [125]. In rheumatoid arthritis patients, IFX lowers circulating TNF levels and improves sleep [126].…”
Section: Sleep/wake Effects Of Prescribed Tnf-active Substancesmentioning
confidence: 99%
“…IFX is a chimeric anti-human TNF monoclonal antibody [124] use to treat autoimmune diseases [125]. In rheumatoid arthritis patients, IFX lowers circulating TNF levels and improves sleep [126].…”
Section: Sleep/wake Effects Of Prescribed Tnf-active Substancesmentioning
confidence: 99%
“…One patient developed drug-induced lupus erythematosus. Vaz et al 38 reported in a multicenter study that infliximab for various diseases induced a significant increase in the number of patients with antinuclear antibody and anti-dsDNA. Momen et al 39 recently reviewed 80 patients who developed TNF-a inhibitor-induced lupus.…”
Section: Lupusmentioning
confidence: 99%
“…However, tumour necrosis factor (TNF)‐α inhibitor therapy in severe lichenoid dermatitis resulting from cancer immunotherapy should be used with caution, as some of these cases may represent early‐stage autoimmune disease. TNF‐α inhibitors impact the formation of lupus autoantibodies and can induce or exacerbate cutaneous autoimmune disease . Treatment with infliximab may have perpetuated SCLE in our second patient and contributed to her positive serologies.…”
Section: Discussionmentioning
confidence: 78%